Analisis Sistem Manajemen Transportasi Darat Berbasis Web Menggunakan Metode Swot pada Balai Pengelola Transportasi Darat Sumatera Selatan - Rio Zuhriansyah; Tata Sutabri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The web-based land transportation management system is a modern solution for managing transportation operations by utilizing web technology to facilitate monitoring, scheduling, and optimization of fleet usage. This study aims to analyze the strengths, weaknesses, opportunities, and threats in the implementation of a web-based land transportation management system using SWOT analysis. The results of this study are expected to serve as a guide for companies or transportation management agencies in designing and developing efficient and effective systems. Although there are several challenges, such as dependency on stable internet infrastructure and relatively high implementation costs, the potential benefits, such as increased operational efficiency, cost reduction, and improved customer service quality, make this system highly relevant and have strong prospects for application in the land transportation industry.